3H-batrachotoxinin-A benzoate binding to voltage-sensitive sodium channels: inhibition by the channel blockers tetrodotoxin and saxitoxin - Brown, GB (J Neurosci, 1986)
The sodium channel blockers tetrodotoxin (TTX) and saxitoxin (STX) and the channel activator batrachotoxin (BTX) produce their effects by binding to separate and distinct sites on the channel protein. The fact that TTX- and STX-modified sodium channels are blocked to sodium flux has precluded drawing any direct conclusions regarding the effect of TTX/STX on BTX binding based on electrophysiological or 22Na flux measurements. Nevertheless, these sites have been presumed to be non- interacting. In this study, 3H-batrachotoxinin-A benzoate (BTX-B), a tritiated congener of BTX, has been used to provide a direct assessment of these binding interactions. Equilibrium specific binding of 3H-BTX-B to sodium channels in vesicular preparations of mouse brain in the presence of scorpion toxin was measured using a filtration assay procedure. At 25 degrees C both TTX and STX inhibit 3H-BTX-B binding in a concentration-dependent and noncompetitive manner. This inhibition is markedly temperature-dependent, being negligible at 37 degrees C and maximal at 18 degrees C, the lowest temperature investigated. Scatchard analysis of BTX-B binding isotherms at 25 degrees C in the presence and absence of 1 microM TTX revealed that inhibition is due to a 3-fold decrease in the affinity of BTX-B binding with no change in the number of binding sites (Bmax). The concentration dependence for TTX inhibition of both specific 3H-STX and 3H-BTX-B binding is identical, suggesting that inhibition of 3H-BTX-B binding is due to a direct effect of TTX/STX binding at their specific sodium channel site. The channel blockers did not alter the binding of scorpion toxin under these assay conditions, nor did BTX-B affect the binding of 3H- STX.(ABSTRACT TRUNCATED AT 250 WORDS)